Cell cycle: a complex network of signals regulating cell proliferation - Giordano, Antonio (Henry Stewart Talks, 2009)
The cell cycle is a complex system which is highly regulated in a temporal manner, via checkpoints and positive and negative feedback loops, Two processes must alternate during eukaryotic cell division: S-phase and M-phase entry, Cell cycle checkpoints, The cell cycle engine, Cyclin D-CDK activity, Not all CDKs and cyclins are involved in the regulation of cell cycle, Cell cycle and pRb family proteins, Cell cycle control pathways